2013
DOI: 10.7314/apjcp.2013.14.5.3351
|View full text |Cite
|
Sign up to set email alerts
|

Benzochloroporphyrin Derivative Induced Cytotoxicity and Inhibition of Tumor Recurrence During Photodynamic Therapy for Osteosarcoma

Abstract: Photodynamic therapy (PDT) is a promising cancer treatment modality that uses dye-sensitized photooxidation of biologic matter in target tissue. This study explored effects of the photosensitizer BCPD-17 during PDT for osteosarcoma. LM-8 osteosarcoma cells were treated with BCPD-17 and cell viability after laser irradiation was assessed in vitro with the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay. The effects of BCPD-17 during PDT recurrence were then examined on tumor-bearing mice in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Among all the three components, photosensitizer is an important element in PDT, currently numerous photosensitizers have been developed and several kinds of photosensitizers have been tested on osteosarcoma cells and showed good photodynamic activities , however, only few photosensitizers have been clinically approved. Therefore, it is critical to put emphasis on existing and undervalued photosensitizers .…”
Section: Introductionmentioning
confidence: 99%
“…Among all the three components, photosensitizer is an important element in PDT, currently numerous photosensitizers have been developed and several kinds of photosensitizers have been tested on osteosarcoma cells and showed good photodynamic activities , however, only few photosensitizers have been clinically approved. Therefore, it is critical to put emphasis on existing and undervalued photosensitizers .…”
Section: Introductionmentioning
confidence: 99%
“…The PDT capability to affect OS tumor size by apoptosis was demonstrated also by Sun’s studies with hiporfin-PDT in OS [144], and benzochloroporphyrin derivative 18-PDT (BCPD18-PDT) on Ewing sarcoma [145] and by Zeng’s studies on hematoporphyrin monomethyl ether-PDT (HMME-PDT) combination in mouse models [148]. Furthermore, the association of PDT with BCPD-17 suppresses local recurrence after tumor resection [136]. The effects of PDT combined with different photosensitizer are confirmed by Yu et al [153,154] studies, showing that ZnPc/BSA-PDT (zinc phthalocyanine BSA conjugated) and PPZ-PDT (PEG-PMAN/ZnPC) were able to reduce tumor size when used intraoperatively; moreover they were able to reduce cell invasiveness in vitro.…”
Section: Application Of Biophysical Therapies In Osteosarcomamentioning
confidence: 99%
“…Several preclinical in vitro and in vivo studies in OS showed that PDT is able to induce apoptosis (activation of mitochondrial and/or caspase pathways, and/or ROS increase), autophagy (activation of ROS-Jnk signaling pathway) and/or to arrest cells at the G2/M phase, depending on PS employed (Table 4) [136,137,138,139,140,141,142,143,144,145,146,147,148]. In addition, PDT can be employed in combination with other biophysical stimuli: low-level light therapy (LLLT) combined with N-aspartyl chlorin e6-PDT (NPe6-PDT) to enhance the cytotoxicity in MG-63 cells by increasing ROS and ATP [149].…”
Section: Application Of Biophysical Therapies In Osteosarcomamentioning
confidence: 99%
“…To solve the synthetic problem in the preparation of biologically active BPD-MA and reduce the toxicity to normal tissues, Yao et al designed and synthesized a novel PS derived from benzochloroporphyrin (BCPD) [ 113 ]. After marginal resection of subcutaneous mice tumors caused by the inoculation of a high-metastatic murine osteosarcoma (LM-8) cell line, BCPD-PDT reduced the local recurrence rate and preserved the adjacent critical anatomic structures including muscles, nerves, and vessels [ 114 ]. In addition, another report from the same team indicated that BCPD-PDT induced the apoptosis and the cell cycle arrest at the G2M phase of human Ewing sarcoma (TC-71) cells.…”
Section: Application Of Pdt In Bone Cancermentioning
confidence: 99%